2009
DOI: 10.1016/j.compenvurbsys.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ontological modelling and Bayesian inference for pattern classification in topographic vector data

Abstract: This paper presents an ontology-driven approach for spatial database enrichment in support of map generalisation. Ontology-driven spatial database enrichment is a promising means to provide better transparency, flexibility and reusability in comparison to purely algorithmic approaches. Geographic concepts manifested in spatial patterns are formalised by means of ontologies that are used to trigger appropriate low level pattern recognition techniques. The paper focuses on inference in the presence of vagueness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 18 publications
0
47
0
1
Order By: Relevance
“…For example, collinear patterns have been extensively investigated (Boffet andRocca Serra, 2001, Christophe andRuas, 2002) in order to simplify and typify building groups. An approach to detect higher-level semantics like terraced house (Lüscher et al, 2009) made use of detected building alignments; the detection approach is however not widely applicable as the buildings in their case was topologically adjacent, which is not commonly the case. Therefore, a more comprehensive view of which building patterns are available, and a generic approach to detect and characterize them are required.…”
Section: Introductionmentioning
confidence: 99%
“…For example, collinear patterns have been extensively investigated (Boffet andRocca Serra, 2001, Christophe andRuas, 2002) in order to simplify and typify building groups. An approach to detect higher-level semantics like terraced house (Lüscher et al, 2009) made use of detected building alignments; the detection approach is however not widely applicable as the buildings in their case was topologically adjacent, which is not commonly the case. Therefore, a more comprehensive view of which building patterns are available, and a generic approach to detect and characterize them are required.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16] proposed algorithms for detecting align-along-road and unstructured building patterns. Luscher et al [19] demonstrated that higher level semantics, such as terraced house, can be derived from building alignments and other criteria. Haunert [20] proposed a methodology for detecting symmetries in building footprints.…”
Section: Implicit Spatial Informationmentioning
confidence: 99%
“…This is necessary, since free form sketching by the user requires the platform to recognize what the user wants to draw and, eventually, provide drawing support. The generation and utilization of ontologies together with Bayesian inference methods may yield a promising approach for such object and context recognition (Alvarado & Davis, 2004;Lüscher, Weibel, & Burghardt, 2009;Yin, Chang, & Forbus, 2010).…”
Section: Research Needs For Participatory Planning Platformsmentioning
confidence: 99%